Fragments of totality futurism, fascism, and the sculptural avant-garde - Merjian, Ara H. 1974- (Yale University Press, 2024)
As the first comprehensive avant-garde of the twentieth century, Italian Futurism sought to integrate modern life with every imaginable aesthetic medium. The detached materiality of sculpture offered a singular proving ground for the drive to merge art and existence. Sculpture’s theory and practice offers a distillation of Futurism’s larger aims and frustrations: a will to mechanize haunted by the tradition of craft; the liberation of flight burdened by mass and gravity; the lyrical mutiny of form chastened by the exigencies of design; and a dream of totality splintered by the contingency of the fragment. Centered on avant-garde sculpture in Italy and other European countries between the world wars, Fragments of Totality ventures a new history of Futurism and its fraught ideological ambitions. Illuminating understudied works by prominent artists like Giacomo Balla, Enrico Prampolini, Fortunato Depero, and Bruno Munari alongside the efforts of many lesser-known figures, this first major study of Futurist sculpture opens onto wider questions: from labor and leftist Futurism, to the politics of aesthetic autonomy, to the intersections between race, imperialism, and materials. The medium—and the idea—of sculpture sets into relief the demands of any project of modern cultural totality. Futurism’s shifting definitions of "plasticity" underscore the volatile political economy not only of interwar Italy, but also perhaps of a wider Western epoch
Keywords: Avantgarde; Faschismus; Futurismus; Plastik; Italien